In situ sonochemical synthesis of ZnO particles embedded in a thermoplastic matrix for biomedical applications - Corrales Urena, Yendry Regina [UNESP]; Prado Bettini, Silvia Helena; Munoz, Pablo Riveros; Wittig, Linda; Rischka, Klaus; Lisboa-Filho, Paulo N. [UNESP] (Elsevier B.V., 2015)
Zinc oxide particles were synthesized and dispersed in situ in a polystyrene (PS) matrix using ultrasound. PS ultrasonic degradation was investigated at different polymer concentrations in organic solvent in contact with aqueous media prior to the particle synthesis. Decrease in weight-average molecular weight (Mw) was strongly dependent on polymer concentration in organic solvent and sonication time: degradation occurred less at higher polymer concentration, yet increased with longer times of more than 30 min. The ZnO particles with a 800 nm flower-like morphology were dispersed in the polystyrene matrix in situ; the composite presented both a lower average molecular weight (M-w) and lower number average molecular weight M-n when compared to pristine polystyrene, however thermal degradation temperature and Young's modulus were similar to the pristine polystyrene. The composite prepared in situ presented lower particle aggregation in comparison with ZnO commercially dispersed with ultrasound under the same conditions. Antibacterial activity of the ZnO/PS coating was tested against Escherichia coil (Gram-negative bacteria; DMS No. 10290) by evaluating bacterial growth inhibition after 20 h on contact with the film surface. The results indicated that bacterial growth was inhibited in the medium in contact with the composite prepared in situ compared to the film of composite prepared by mixing and the pristine PS. This study showed the potential use of ZnO/PS composite prepared in situ as antibacterial coatings. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ultrasound; Polystyrene; Degradation; Zinc oxide; In situ; Antibacterial activity